GLB prevents tumor metastasis of Lewis lung carcinoma by inhibiting tumor adhesion actions - Pan Yan; Song Qian-liu; Lin Yan-hua; Lu Ning; Yu He-ming; Li Xue-jun (Acta Pharmacologica Sinica; Vol 26, No 7 (July 2005): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the inhibitory effect of a new compound of GLB on tumor metastasis in vivo and analyze its actions on tumor cell adhesion to clarify its mechanism. Methods: The effect of GLB on tumor metastasis was analyzed by Lewis lung carcinoma model. The pathological morphology of lung alveolar was evaluated by hematoxylin-eosin staining. The effect of GLB on the proliferation of human prostate cancer cell (PC-3M, with a high metastatic characteristic) was studied using the MTT method, and its actions on PC-3M cell adhesion to human umbilical vein endothelial cells (HUVEC) and laminin were analyzed in vivo. Results: GLB (100 mgdotkg-1dotd-1 for 28 d, ig) reduced the number of lung colonies of Lewis lung carcinoma metastasis significantly (P < 0.05). Simultaneously, GLB could mitigate the damage of lung alveolar caused by metastasic tumor deposits. in vivo, GLB inhibited dramatically the adhesion of PC-3M cells to HUVEC (P < 0.01) and laminin (P < 0.05), without cytotoxic or anti-proliferative action on PC-3M cells. Conclusion: GLB has anti-tumor metastatic activity, which partly depends on its inhibition of tumor adhesion.